Sentidos e motivações da restrição à participação social em pessoas afetadas pela hanseníase no munícipio de Vitória da Conquista – BA, no período de 2001 a 2014 - Castilhano, Andréia Alves (2017)
Leprosy, as a chronic and stigmatizing disease, can contribute to social isolation and, therefore, characterize the social participation of people affected by the disease. The association with disability and stigma can serve as a sizing of their impacts. This study aimed to understand the meanings and motivations of the restriction to social participation in people affected by leprosy in the municipality of Vitória da Conquista -Ba, from 2001 to 2014. This is a cross -sectional study with two descriptive temporal sections, with a qualitative nested. Includes post-discharge cases, reported in the SINAN Notification System Information System, from 2001 to 2014, of the residents of the urban area of the city of Vitória da Conquista-Ba. It was carried out in two phases: phase one, of quantitative nature, with sociodemographic, clinical characterization and participation restriction. And phase two, qualitative, included the understanding of the expression of people who presented some restriction to participation in phase one. In order to conduct the interview, a road map was created based on the International Classification of Functioning, Disability and Health (CIF) domains contemplated in the Participation Scale. For analysis of the quantitative data, univariate analysis of sociodemographic and clinical variables was used. In the qualitative analysis, the thematic analysis modality was used. Among those evaluated in stage one (n = 193), 55.4% were women, 56% declared themselves to be of brown race, 61.1% were concentrated in the economically active age group, from 15 to 59 years. Regarding clinical aspects (n = 190), 53.2% were classified as multibacillary, 34.7% were clinical form Dimorfa; 46.6% presented leprosy reaction. In the neurological evaluation performed (n = 184), it was found that 60.9% had some disability,43.5% were classified as grade 1 and 17.4% in grade 2. Regarding social participation (n = 173), 24.9% of the people presented some restriction. For phase two, the scale was reapplied in 15 people, observing a reduction in the restriction in 60% of them. Seven people were interviewed for understanding the restriction. Of the eight domains of the CIF that base the Participation Scale, only the domestic life domain was not contemplated. Seven thematic categories emerged: learning and applying knowledge, communication, mobility, personal care, interactions and interpersonal relationships, major areas of life, community, social and civic life. The qualitative approach to understanding the reasons for the restriction, based on the roadmap constructed in this study, allows us to assess which domain is affected and whether there is a relationship between leprosy and restriction. In this study, it was noticed that the domains most affected in the people interviewed were "Interpersonal relations and interactions", "Community, social and civic life" and "Major areas of life". Thus, the discourses show that the reasons for the restriction were due to the stigma suffered due to leprosy and to the impossibility of performing work activities due to physical incapacities or presence of leprosy reaction. It is hoped that this study will provide subsidies to promote the decentralization of care to those affected, to insert the use of the Participation Scale in the routine of care and to carry out a protocol to refer to the psychological and social needs, guaranteeing the integrality of care.